THE EFFECT OF REBRANDING ON IMAGE OF NEO COMMERCE BANK DURING THE PANDEMIC COVID 19 SURVEY OF JAKARTA GOZCO CUSTOMERS - Febrianto, Anggi; Atmodjo, Juwono Tri; Suraya, Suraya (International Journal of Social and Management Studies, 2023)
The Covid 19 pandemic is not just a pandemic but also became a catalyst for various business lines to innovate in order to survive and compete with competitors, Bank Yudha Bhakti now known as Bank Neo Commerce (BNC) is one of the banks that took the Rebranding to deal with Covid 19 exposure. thus objective of this research is to find out how far the change in name, logo, slogan and service has affected the company's image for BNC KCU Jakarta Gozco customers.Some of the theories that serve as tools in this research are systems theory which explains that rebranding or changes that occur within the organization as a result of environmental influences at the same time assessed as an adaptation mechanism which is clarified by organizational communication theory and corporate image theory in the context of corporate communication goals towards external audience to meet customer expectations. This study uses rebranding as an independent variable they are Name, Logo, Slogan and Service on its influence on Company Image as Variable Y. This study used a quantitative approach with a survey method by distributing questionnaires to 180 samples. The type or nature of this research is associative, causal, in this study BNC wants to convey its goal that they have turned into a digital bank through rebranding.The conclusion of this study is that the significance value for the Name variable (X1) to Image (Y) is 0.357> 0.05 and the t-count value to the t table of Name Variable (X1) is 0.923 <1.973 so that the name change has no significant effect, then for the Variable Logo (X2) has a significance value of 0.429> 0.05 and the value of t count to t table is 0.793 <1.973 in other words changes in the logo do not significantly affect BNC image, then Slogan (X3) has a significance value of 0.02 <0.05 while the t count value for the t table is 3.175> 1.973 so that changes in the Slogan have a significant effect on the Image of the Neo Commerce Bank, Service (X4) gets a significance value of 0.00 <0.05 and the t count value on the t table is 3.958> 1.973 so that the change in Slogan has a significant effect to the BNC Image, then simultaneously X1, X2, X3, and X4 to Y have a significance value of 0.000 <0.005 and a calculated F value of 39.702> 2.42 it can be concluded that the change in Name, Logo , Slogan, and Services simultaneously have a significant effect on the BNC Image of Jakarta Gozco KCU customers.